2013
DOI: 10.3399/bjgp13x668159
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the predictive value of HIV indicator conditions in general practice: a case–control study using the THIN database

Abstract: BackgroundUK HIV guidelines identify 37 clinical indicator conditions for adult HIV infection that should prompt an HIV test. However, few data currently exist to show their predictive value in identifying undiagnosed HIV. AimTo identify symptoms and clinical diagnoses associated with HIV infection and assess their relative importance in identifying HIV cases, using data from The Health Improvement Network (THIN) general practice database. Design and settingA case-control study in primary care. MethodCases (HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…17,24 The types of indicator conditions observed in this review correlate well with existing literature, 17,18,24 stressing the importance of focusing education and training on HIVassociated disease that is commonly seen in general practice. To the authors' knowledge, this study is the first large scale review of accuracy of GP ART recording and so data comparisons are not possible.…”
Section: Comparison With Existing Literaturesupporting
confidence: 58%
“…17,24 The types of indicator conditions observed in this review correlate well with existing literature, 17,18,24 stressing the importance of focusing education and training on HIVassociated disease that is commonly seen in general practice. To the authors' knowledge, this study is the first large scale review of accuracy of GP ART recording and so data comparisons are not possible.…”
Section: Comparison With Existing Literaturesupporting
confidence: 58%
“…A Dutch case-control pilot study showed that more than half of all cases (58.5%) in a high-prevalence area had one or more ICs in the five years prior to HIV diagnosis [21]. A UK general practice case-control study found that 25.8% of HIV cases had presented with an ICs one year prior to the HIV diagnosis date [20]. In our study, 44.2% of cases had one or more ICs one year prior to the HIV diagnosis date.…”
Section: Discussionmentioning
confidence: 99%
“…A UK case-control study in primary care found multiple ICs that were associated with a subsequent HIV diagnosis [20]. …”
Section: Introductionmentioning
confidence: 99%
“…A large Italian cohort showed the importance of testing for HIV following the diagnosis of HIV indicator conditions, as this significantly decreases the probability of late HIV diagnosis 20. A UK general practice case–control study found that 25.8% of HIV cases had presented with one or more HIV indicator conditions 1 year prior to receiving a diagnosis of HIV 21. In our study, we found that 58.8% of the HIV cases had HIV indicator conditions in the 5 years prior to HIV diagnosis.…”
Section: Discussionmentioning
confidence: 99%